First ultrastructural and cytochemical data on the spermatozoon and its differentiation in progenetic and adult Archigetes sieboldi Leuckart, 1878 (Cestoda, Caryophyllidea, Caryophyllaeidae) - Bruňanská, Magdaléna; Matoušková, Martina; Nebesářová, Jana; Mackiewicz, John S; Poddubnaya, Larisa G (Parasitology research, 2019)
Spermiogenesis in progenetic and adult stages of Archigetes sieboldi Leuckart, 1878, a tapeworm parasitic in oligochaetes and fish respectively, has been examined using transmission electron microscopy and cytochemical staining for glycogen. General pattern of spermiogenesis is essentially like that of other caryophyllideans, i.e., apical dense material in the zone of differentiation in the early stages of spermiogenesis, rotation of free flagellum and a flagellar bud, and proximo-distal fusion. Interestingly, rotation of a free flagellum and flagellar bud to the median cytoplasmic process (MCP) has been observed unconventionally at > 90° only in progenetic stages. Typical striated roots associated with the centrioles occur rarely in A. sieboldi, and only in form of faint structures in advanced stages of spermiogenesis. In contrast to most caryophyllideans studied to date, penetration of the nucleus into the spermatid body has started before the fusion of the free flagellum with the MCP. This feature has been reported rarely but exclusively in the family Caryophyllaeidae. The unipartite mature spermatozoon of A. sieboldi is composed of one axoneme of the 9 + '1' trepaxonematan pattern with its centriole, parallel nucleus, and parallel cortical microtubules which are situated in a moderately electron-dense cytoplasm with glycogen particles. An unusual arrangement of cortical microtubules in the two parallel rows in region I of the spermatozoon is described here for the first time in the Caryophyllidea. Ultrastructural data on spermiogenesis and the spermatozoon in A. sieboldi from tubuficids and carp are compared and discussed with those in other caryophyllideans and/or Neodermata.
Keywords: buněčné jádro; cestodózy; Carps; Cestoda; Fish Diseases; Cell Nucleus; zvířata; transmisní elektronová mikroskopie; Spermatids; spermatidy; Spermatogenesis; kapři; glykogen; Glycogen; mužské pohlaví; barvení a značení; Microscopy, Electron, Transmission; nemoci ryb; Staining and Labeling; flagella; Axoneme; spermatogeneze; axonema; Animals; Flagella; Male; Cestode Infections